2016
DOI: 10.1111/jnc.13704
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disruption of secondary binding site S2 on dopamine transporter function

Abstract: The structures of the leucine transporter, drosophila dopamine transporter, and human serotonin transporter show a secondary binding site (designated S2) for drugs and substrate in the extracellular vestibule towards the membrane exterior in relation to the primary substrate recognition site (S1). The present experiments are aimed at disrupting S2 by mutating Asp476 and Ile159 to Ala. Both mutants displayed a profound decrease in [3H]DA uptake compared with wild-type associated with a reduced turnover rate kca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…This distal "S2" site is hypothesized to facilitate binding of substrate to the primary substrate site (Nyola et al, 2010) and possibly even drive the translocation of the dopamine molecule across the membrane (Shan et al, 2011). A potential interaction with the S2 site was assessed with recently described mutants containing disruptions in the S2 site by mutation of Asp476 and Ile159 to Ala (D476A and I159A, respectively) (Zhen and Reith, 2016). Previously, we reported that the K d for binding of [ 3 H]WIN 35,428 to the DAT in WT and the two S2 mutants was the same, whereas the ability of dopamine in competing for [ 3 H]WIN 35,428 binding was reduced in the mutants (Zhen and Reith, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This distal "S2" site is hypothesized to facilitate binding of substrate to the primary substrate site (Nyola et al, 2010) and possibly even drive the translocation of the dopamine molecule across the membrane (Shan et al, 2011). A potential interaction with the S2 site was assessed with recently described mutants containing disruptions in the S2 site by mutation of Asp476 and Ile159 to Ala (D476A and I159A, respectively) (Zhen and Reith, 2016). Previously, we reported that the K d for binding of [ 3 H]WIN 35,428 to the DAT in WT and the two S2 mutants was the same, whereas the ability of dopamine in competing for [ 3 H]WIN 35,428 binding was reduced in the mutants (Zhen and Reith, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A potential interaction with the S2 site was assessed with recently described mutants containing disruptions in the S2 site by mutation of Asp476 and Ile159 to Ala (D476A and I159A, respectively) (Zhen and Reith, 2016). Previously, we reported that the K d for binding of [ 3 H]WIN 35,428 to the DAT in WT and the two S2 mutants was the same, whereas the ability of dopamine in competing for [ 3 H]WIN 35,428 binding was reduced in the mutants (Zhen and Reith, 2016). This is consonant with an allosteric effect of S2 site disruption on S1 site functionality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the diphenyl structural motif in 6c could partially account for its blockade of dopamine uptake because this motif also exists in atypical DAT blockers such as modafinil and benztropine, which appear to bind preferentially to the inward-facing conformation of DAT (Reith et al, 2015;Schmitt et al, 2013). In addition to the well-characterized substrate site (S1), crystal structures of the bacterial leucine transporter (Zhen and Reith, 2016), the drosophila DAT, and the serotonin transporter show the presence of secondary allosteric sites (S2 and S3), where compounds can bind and modify the conformation and function of DAT (Reith et al, 2015;Schmitt et al, 2013). It is possible that 6c could occupy one of these allosteric sites.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to explain this paradox are often pharmacokinetic in nature: of the three drugs, only cocaine reaches the brain fast enough at high concentration to trigger the phasic firing of accumbal dopamine cells needed to elicit euphoria. 1518 From cysteine accessibility studies, an alternative explanation arose from the finding that cocaine and benztropine bind to different DAT conformations. 1921 Because cocaine recognizes the OF conformation and benztropine recognizes the IF conformation, it was postulated that behaviorally “typical” (abusable, locomotor psychostimulant) inhibitors such as cocaine stabilize the OF DAT and “atypical” (little or no abuse potential) inhibitors favor IF DAT.…”
Section: Introductionmentioning
confidence: 99%